2012
DOI: 10.1002/chem.201200828
|View full text |Cite
|
Sign up to set email alerts
|

From an Icosahedron to a Plane: Flattening Dodecaiodo‐dodecaborate by Successive Stripping of Iodine

Abstract: It has been shown by electrospray ionisation-ion trap mass spectrometry that B 12 I 12 2-converts to an intact B 12 cluster as a result of successive stripping of single iodine radicals or ions. Here we report the structure and stability of all intermediate B 12 I n -species (n = 11 to 1) determined by means of firstprinciples calculations. The initial predominant loss of an iodine radical occurs most probably via the triplet state of B 12 I 12 2-, and the reaction path for loss of an iodide ion from the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
3
29
0
1
Order By: Relevance
“…Therefore, we computed the Gibbs free energies, ΔG, for both open-and close-B12X7 − at 300, 1500, and 5000 K, through the harmonic approximations for the minimum structures on the potential energy surface at 0 K. The Gibbs free energies were computed by ΔG = Gico -Gope = ΔU + RT -TΔS (U is the internal energy, T is the temperature, R is the gas constant and S is the entropy), and the data are given in Table 1. Previously, it was found that for the B12 cluster with seven iodine substituents, the temperature dependence of ΔG is important, 9 and here we have found the same phenomenon. cage.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, we computed the Gibbs free energies, ΔG, for both open-and close-B12X7 − at 300, 1500, and 5000 K, through the harmonic approximations for the minimum structures on the potential energy surface at 0 K. The Gibbs free energies were computed by ΔG = Gico -Gope = ΔU + RT -TΔS (U is the internal energy, T is the temperature, R is the gas constant and S is the entropy), and the data are given in Table 1. Previously, it was found that for the B12 cluster with seven iodine substituents, the temperature dependence of ΔG is important, 9 and here we have found the same phenomenon. cage.…”
Section: Resultssupporting
confidence: 88%
“…The transition between the icosahedral and planar structures is found be n = 5 to 7 depending on the temperatures. 9 Later, a combined experimental and theoretical infrared (IR) spectroscopy study was carried out to narrow down the region of transition. 19 The results showed that the simulated IR spectra matches the experimental IR spectra based on the icosahedral structures for n ≥ 8.…”
Section: Introductionmentioning
confidence: 99%
“…Upon substitution with halogen atoms, this 2D‐to‐3D structural transition occurs earlier with fewer boron atoms. For example, a B 12 cluster was confirmed to be a bowl‐shaped quasi‐planar structure, but it preferred to be a 3D cage structure when more seven iodine atoms were substituted . The earlier 2D‐to‐3D transition in anionic boron clusters also occurs upon addition of transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…In the solid state, boron compounds often adopt threedimensional (3D) structures [6][7][8][9][10]. One heavily studied type is boranes of general form B n H n .…”
Section: Planar Boron Clustersmentioning
confidence: 99%
“…In this circular planar structure, a central boron atom is surrounded by a pentagonal unit, which is directly bonded to the outer B 13 ring. Interestingly, AdNDP (Adaptive Natural Density Partitioning) chemical bonding analysis showed that this cluster is characterized by a unique double π-aromaticity involving ten π-electrons delocalized between the inner pentagon and the outer B 13 ring, similar to the case of cyclodecapentaene, and another two π-electrons delocalized over the central B 6 , and B 30 − anions are also confirmed to be planar [20][21][22][23]. The chemical bonding analysis reveals that the bonding in B 22 − is similar to that in anthracene, and the bonding in B 23 − is analogous to that in phenanthrene.…”
Section: Planar Boron Clustersmentioning
confidence: 99%